Peran Analisis Penerapan Metode Gross Up, Gross dan Net Perhitungan PPh Pasal 21 Karyawan Struktural Menggunakan Tarif Efektif Rata-Rata (TER) terhadap PPh Badan pada Rumah Sakit X - Rizki Zada Maulana Putra; Puji Rahayu; Miladiah Kusumaningarti (International Forum of Researchers and Lecturers, 2026)
This study examines the calculation of Income Tax Article 21 (PPh 21) for structural employees using the Average Effective Rate (TER) and analyzes its impact on Corporate Income Tax at Hospital X. The research applies a quantitative case study approach using secondary data obtained from the 2024 payroll records of 15 structural employees. The calculation of PPh 21 was carried out using three taxation methods, namely the gross, net, and gross-up methods. The results of each method were then compared to evaluate their influence on employee tax obligations, fiscal profit, and Corporate Income Tax. The findings reveal that both the gross and net methods produced the same PPh 21 amount of Rp45,223,900, while the gross-up method generated a higher tax amount of Rp53,112,150 due to the provision of tax allowances. Despite increasing the amount of PPh 21, the gross-up method enables tax allowances to be recognized as deductible operating expenses, thereby reducing taxable income and the company's Corporate Income Tax liability. Consequently, the gross-up method is considered the most effective tax planning strategy because it enhances tax efficiency, complies with prevailing tax regulations, and simultaneously improves employee welfare through the provision of tax benefits.